Risking work and working risk : a phenomenology of the risk environment of prostitution in Ireland - McGarry, Kathryn (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2009)
The focus of this thesis is on the lived experiences of women in prostitution in Ireland. The limited knowledge base on the Uved realities of those engaged in prostitution in Ireland was a compelling rationale for undertaking this study. Previous Irish research (O'Connor, 1996) has pointed to the negative impact of the criminalised system of prostitution in Ireland on the experiences of those engaged in sex work. This study set out to explore how those engaged in prostitution negotiate their lives within this context through a phenomenological methodology. The research developed around a broad discursive paradigm which considered the different contextual levels at which prostitution is understood, from macro level discourses of prostitution to the women’s own discourses. Snowball sampling recruited thirteen respondents with experience of prostitution in Ireland, eleven street workers and two indoor workers, and their accounts of their experiences were collected through qualitative in-depth interviewing. Additional ‘context setting’ data was obtained from qualitative semi-structured interviews with ten key informants working in the area of prostitution.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin